A Review Study on Chillies as Food (International Journal of Innovative Research in Computer Science & Technology, 2021)
Chilies are made up of nonvolatile ether  soluble extractives from dried ripe Capsicum fruits. It's an  annum line. var: minimum, family member Chili Solanaceae  is an important crop in soup preparation. It has a minimum  of 12% sauce, spicy water, and other ingredients in the  nation. Chilies have been utilized as a portion of food, flavor,  and family medication for an assortment of sicknesses since  old times, including elevated cholesterol, hypertension, joint  torment, skin issues, and as a carminative, tidbit, stomachic,  refreshments, relief from discomfort in neuropathy, and counter aggravation in the therapy of stiffness and lumbago.  Its organic design is to stop herbivorous creatures, parasites,  and different microorganisms. The expression "capsicum"  comes from the Greek word "kapsimo," and that signifies "to  chomp". Capsaicin, protein, fixed oil, thiamine, and ascorbic  corrosive are answerable for chilies' restorative impacts. This  paper examines pharmacognosy, pharmacology, and their  beneficial benefits, as well as numerous herbal formulae for  various illnesses, chili preparations, commercial  formulations, and their main adverse effects or  contraindications.
Keywords: Chilies; Capsaicin; Health; Pharmacognosy; Pharmacology